Traumatic retinopathy presenting as acute macular neuroretinopathy. Issue 10 (12th July 2013) - Nentwich, Martin M; Leys, Anita; Cramer, Andreas; Ulbig, Michael W
Abstract : Aim: Traumatic retinopathy presenting as acute macular neuroretinopathy (AMNR) is an uncommon disease causing paracentral scotomas after indirect trauma. Methods: We report on five patients (six eyes) with AMNR with a temporary reduction of visual acuity and persistent paracentral scotomas after indirect trauma. The findings were documented using multimodal imaging and the follow-up was up to 32 months. Results: Initially, fundoscopy was unremarkable in all patients while visual acuity (Snellen equivalents) varied between 0.03 and 1.0, and a paracentral scotoma was present in all patients. During follow-up, visual acuity recovered to 1.0 in all patients while the paracentral scotomas persisted. Spectral-domain optical coherence tomography revealed a disruption of the inner/outer segment junction within the macular lesion and changes in the outer nuclear layer, which slowly recovered partly during the follow-up. Conclusions: These findings suggest that indirect trauma can cause changes in the outer retina resembling those seen in AMNR, resulting in persisting paracentral scotomas.